Evidence of reduced bladder capacity during nighttime in children with monosymptomatic nocturnal enuresis. Issue 2 (April 2018) - Borg, B.; Kamperis, K.; Olsen, L.H.; Rittig, S.
Summary: Introduction: Bladder capacity in children with nocturnal enuresis is assessed by maximal voided volumes (MVV) obtained through daytime frequency volume (FV) charts. Although a degree of association has been demonstrated, daytime MVV does not consistently correspond with the nocturnal bladder capacity (NBC) in monosymptomatic nocturnal enuresis (MNE). It was hypothesized that isolated reduced NBC is a common phenomenon in children with nocturnal enuresis, despite normal daytime bladder function. Objective: The aim of this study was to evaluate NBC in children with MNE and normal daytime voided volumes. Specifically, it aimed to determine the prevalence and degree of reduced NBC when using nocturnal urine production (NUP) during wet nights as a surrogate estimate of NBC. Furthermore, it aimed to investigate the relationship between NBC and desmopressin response. Materials and methods: Data from 103 children aged 5–15 years consecutively treated for MNE in a tertiary referral centre and with normal MVV on daytime FV charts were collected for this cohort study. Home recordings were completed for 2 weeks at baseline and during desmopressin dose titration. Estimated nocturnal bladder capacity (eNBC) was assessed separately each night as the total NUP causing a wet night. If NUP during a wet night was less than MVV, it was considered to be reduced eNBC during that particular night. Results: Surprisingly, 82% ( n = 84) of the children with MNE and normal daytime MVV experienced at least one wet night, with NUP below the daytime MVV indicative of a reduced eNBC. For 84 patients, mean percentage of wet nights with reduced eNBC (NUP below MVV) was 49% (SD ± 31). A total of 11% of children with frequently reduced eNBC (>40% of wet nights with reduced eNBC) responded to desmopressin (Summary Fig.). Of the children with frequently reduced NBC, 91% experienced wet nights, with NUP <65% of expected bladder capacity (EBC). Conclusions: A significant proportion of children with MNE and normal MVV during the daytime frequently experienced wet nights, with a NUP well below their MVV and even <65% of EBC. This indicated that bladder reservoir dysfunction during sleep is relatively common in MNE. This abnormality was not reflected on daytime recordings, and thus nighttime data with NUP must be collected. This phenomenon may explain treatment failure to desmopressin, despite adequate antidiuretic response. Figure Number of desmopressin responders (%) in the three groups of patients. Patients were defined as frequently reduced eNBC if >40% of wet nights were with NUP <MVV.